Nucleotide-Bound Oligomeric Domain-Like Receptor Protein 3 as a Serological Biomarker in Relation to Disease Severity and Delirium After Acute Pancreatitis: A Two-Center Prospective Cohort Study - Tang Z; Zhou X; Rao Y; Wu J (International Journal of General Medicine, 2025)
Zihao Tang,1 Xinwen Zhou,1 Yujun Rao,2 Jianye Wu1 1Department of Gastroenterology, Lishui City Hospital of Traditional Chinese Medicine, Lishui, Zhejiang Province, People’s Republic of China; 2Department of Gastroenterology, Lishui Hospital of Wenzhou Medical University, Lishui People’s Hospital, Lishui, Zhejiang Province, People’s Republic of ChinaCorrespondence: Jianye Wu, Department of Gastroenterology, Lishui City Hospital of Traditional Chinese Medicine, Lishui, Zhejiang Province, People’s Republic of China, Email equest@163.comObjective: Acute pancreatitis (AP) is a very common infectious diseases, with delirium as a conventional complication. Nucleotide-binding oligomeric structural domain-like receptor protein 3 (NLRP3) is involved in inflammatory response after AP. We set out to determine whether serum NLRP3 levels are related to severity and delirium in patients with AP.Methods: In this two-center prospective cohort study, a total of 311 patients with AP were divided to study group and validation group according to the ratio of 2:1, and serum NLRP3 levels were measured in all patients and healthy controls. To assess disease severity, Acute Physiology and Chronic Health Evaluation II (APACHE II), Ranson and Sequential Organ Failure Assessment (SOFA) scores were recorded. Delirium was observed as an outcome variable. Multifactorial analysis was performed to discern severity correlations and outcome correlations. Prediction model containing independent predictors of delirium was constructed in study group and validated in validation group.Results: Serum NLRP3 levels were significantly higher in patients with AP than in controls, and were independently associated with three traditional indicators of AP severity, that is APACHE II scores, Ranson scores, and SOFA scores. When compared with the preceding traditional predictors, serum NLRP3 levels had comparable predictive ability for post-AP delirium. The four predictors were incorporated to create the predictive model of nomogram presentation. The model displayed significantly higher predictive capability than their use alone. In addition, the model was similarly effective for delirium prediction in validation group.Conclusion: Elevated serum NLRP3 levels after AP, in firm correlation with AP severity, independently predict in-hospital delirium, solidifying serum NLRP3 as a candidate for severity assessment and delirium anticipation after AP.Keywords: acute pancreatitis, NLRP3, severity, delirium, serum